A role for pathogenic autoantibodies in small fiber neuropathy? - Daifallah, Omar; Farah, Adham; Dawes, John M. (Frontiers in Molecular Neuroscience, 2023)
The immune system has a role in neuropathic pain which includes autoimmune mechanisms (e.g., autoantibodies). Clinical studies have identified a number of conditions where neuropathic pain is common and that are associated with autoantibodies targeting antigens within the nervous system. Interestingly sensory symptoms can be relieved with immunotherapies or plasma exchange, suggesting that pain in these patients is antibody-mediated. Recent preclinical studies have directly addressed this. For example, passive transfer of CASPR2 autoantibodies from patients cause increased pain sensitivity and enhanced sensory neuron excitability in mice confirming pathogenicity and demonstrating that patient autoantibodies are a mechanism to cause neuropathic pain. Small fiber neuropathy (SFN) exclusively affects small sensory fibers (typically nociceptors) and is characterized by severe neuropathic pain. Known causes include diabetes, B12 deficiency and rare variants in sodium channel genes, although around 50% of cases are idiopathic. SFN is associated with autoimmune conditions such as Sjorgen’s syndrome, Sarcoidosis and Celiac disease and immunotherapy in the form of Intravenous immunoglobulin (IVIG) has proved an effective treatment. Autoantibodies have been identified and, in some cases, passive transfer of SFN patient IgG in mice can recapitulate neuropathic pain-like behavior. Here we will discuss clinical and preclinical data relating to the idea that pathogenic autoantibodies contribute to SNF. We discuss putative pathogenic antibodies, cellular targets and the molecular mechanisms by which they cause sensory neuron damage and the development of neuropathic pain. Finally, we will comment on future directions which may provide further insights into the mechanisms underlying SFN in patients.